(untitled) (Principles and Practice of Clinical Research, 2023)
Background/Aims: Creatine supplementation has demonstrated cognitive benefits in neurodegener-ative conditions, having a protective effect in the brain's function in stressful situations, with excellent safety (Watanabe et al., 2002). However, any beneficial effects on the cognitive performance of healthy adolescents underperforming in school is unknown. Our objective is to assess whether creatine sup-plementation improves cognitive performance in 15- to 17-year-old students with an average school grade below the 50th percentile.Methods: This will be a phase-II, triple-blinded, randomized, parallel-group, superiority, single-center trial. Students with grades below the 50th percentile in the prior semester will be enrolled and random-ized to receive juice packages containing either creatine monohydrate supplementation (0.1 mg/kg/day), or placebo, for 12 weeks. The primary outcome will be the mean difference in change of Raven’s Standard Progressive Matrices (RSPM) scores from baseline to week 12 between groups. To achieve a 90% power for detecting a 3-point difference in change in the RSPM score, and accounting for drop-out, 116 participants will be included. Secondary outcomes will include the difference in pro-cessing speed (SpaceCode), working memory (SpaceMatrix), non-visual memory (backward digit span), percentage change in lean mass, and any safety events. Conclusion: To our knowledge, this will be the most comprehensive study assessing creatine supple-mentation in adolescents. This is a low-risk intervention that has been shown to improve cognitive function in other populations. This study will potentially support the widespread use of creatine sup-plementation in adolescents with low school performance, while having a positive impact on this pop-ulation. Keywords: creatine; adolescents; cognitive function; raven’s progressive matrices.